2005
DOI: 10.1038/sj.jhh.1001820
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension — still an important cause of heart failure?

Abstract: Hypertension has been the single most important risk factor for heart failure until the last few decades. Now, it is frequently claimed that atherosclerotic coronary artery disease dominates as the major underlying cause, and hypertension is of lesser importance. We here review evidence regarding the contribution of hypertension to heart failure in the recent decades. It is not possible, in our view, to be confident of the relative importance of hypertension and coronary artery disease since there are signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…It is an important risk factor that predisposes to cardiovascular diseases, including cardiac failure, stroke, chronic renal failure or coronary artery disease. 1 Like other multifactorial human traits, HT is caused by the interplay of several different 'risk' genes and multiple environmental factors. The risk of acquiring HT increases with the number of affected relatives and with severity of HT in these relatives.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important risk factor that predisposes to cardiovascular diseases, including cardiac failure, stroke, chronic renal failure or coronary artery disease. 1 Like other multifactorial human traits, HT is caused by the interplay of several different 'risk' genes and multiple environmental factors. The risk of acquiring HT increases with the number of affected relatives and with severity of HT in these relatives.…”
Section: Introductionmentioning
confidence: 99%
“…IR is a risk factor for congestive heart failure, independently of established risk factors including diabetes (19). Moreover, IR commonly clusters with other cardiovascular risk factors such as hypertension, a chronic state of pressure-overload that can lead to heart failure (20). We previously developed a mouse model of combined IR and pressure-overload, by feeding mice a high-fat diet (HFD) followed by transverse aortic constriction (TAC) (30).…”
mentioning
confidence: 99%
“…This is most evident for the common conditions that complicate hypertension, such as heart failure and atrial fibrillation. 10,11 If hypertension is indeed caused by, or causes a proinflammatory state, then other inflammatory markers apart from the CRP must also have a role in the pathogenesis of hypertension. Recently, Orakzai et al 12 showed a linear relationship between higher while blood cell counts (WCC) and systolic blood pressures in a Brazilian population.…”
mentioning
confidence: 99%